Next-Generation Sequencing Revealed TP53 Mutations to Be Malignant Marker for Intraductal Papillary Mucinous Neoplasms That Could Be Detected Using Pancreatic Juice. Issue 10 (November 2017) - Takano, Shinichi; Fukasawa, Mitsuharu; Kadokura, Makoto; Shindo, Hiroko; Takahashi, Ei; Hirose, Sumio; Maekawa, Shinya; Mochizuki, Kunio; Kawaida, Hiromichi; Itakura, Jun; Katoh, Ryohei; Fujii, Hideki; et al.
Abstract : Objectives: The aims of this study were to identify the genetic mutations associated with malignant intraductal papillary mucinous neoplasms (IPMNs) and evaluate the possibility of detecting mutations in pure pancreatic juice by next-generation sequencing. Methods: Resected tissues were collected from 50 patients with IPMN, and pure pancreatic juice samples were collected from 19 patients who had a resection. The extracted DNA was amplified by multiplex polymerase chain reaction targeting 52 cancer-related genes, including KRAS, GNAS, RNF43, and TP53 ; the mutations were then detected by next-generation sequencing and then analyzed for correlations with the clinicopathological characteristics. Results: In the resected tissues, the most frequently detected mutations were in KRAS, GNAS, TP53, and RNF43, in 88%, 76%, 36%, and 30% of cases, respectively. Univariate and multivariate analyses revealed that only TP53 mutations were associated with malignant IPMNs ( P = 0.023). In the pure pancreatic juice, TP53 mutations were detected in 5 of 10 resected samples with malignant IPMN and in 4 of 5 pancreatic juice samples with mutation in resected samples. Conclusions: From 52 cancer-related gene analysis, only TP53 mutation was associated with malignant IPMNs. TP53 mutation could also be detected in pure pancreatic juice, potentially making it a useful tool to diagnose malignant IPMNs preoperatively.